Syrian audience attitudes towards electronic advertisements for delivery applications “A field study” (Damascus University Journal of arts and humanities sciences, 2026)
The aim of the research was to study the attitudes of the Syrian public towards electronic advertisements for delivery applications. To achieve this goal, a sample survey was conducted, relying on the electronic questionnaire tool to collect data. The questionnaire was published on social media sites, prepared by the researcher and adopted the five-point Likert scale in its design. A sample of (578) people was reached through it. After collecting the information, it was unpacked and analyzed using the SPSS program. Using appropriate statistical methods, a set of results was reached, the most important of which was that the Syrian public tends to accept electronic advertisements for delivery applications positively. It also showed that the Syrian public's satisfaction with electronic advertisements for delivery applications is positive, but average satisfaction. The results also indicated that the impact of advertisements is relatively weak on the public's use of these applications. It was also found that the most influential factors on attitudes towards advertising are "enjoyment and attractiveness", followed by "credibility", then "providing information". Annoyance negatively affects attitudes towards advertising, which means that increasing the frequency of advertisements or displaying them in an undesirable manner leads to public alienation. At the end of the research, a set of proposals were presented that may contribute to improving the level of electronic advertisements in general, and advertisements for delivery applications in particular.
Keywords: Attitudes; Syrian Audience; Advertisements; Electronic Advertisements; Delivery Applications